A review of respirable fine particulate matter (PM2.5)-induced brain damage - Li, Wei; Lin, Guohui; Xiao, Zaixing; Zhang, Yichuan; Li, Bin; Zhou, Yu; Ma, Yong; Chai, Erqing (Frontiers in Molecular Neuroscience, 2022)
Respirable fine particulate matter (PM2.5) has been one of the most widely publicized indicators of pollution in recent years. Epidemiological studies have established a strong association between PM2.5, lung disease, and cardiovascular disease. Recent studies have shown that PM2.5 is also strongly associated with brain damage, mainly cerebrovascular damage (stroke) and neurological damage to the brain (changes in cognitive function, dementia, psychiatric disorders, etc.). PM2.5 can pass through the lung–gas–blood barrier and the “gut–microbial–brain” axis to cause systemic oxidative stress and inflammation, or directly enter brain tissue via the olfactory nerve, eventually damaging the cerebral blood vessels and brain nerves. It is worth mentioning that there is a time window for PM2.5-induced brain damage to repair itself. However, the exact pathophysiological mechanisms of brain injury and brain repair are not yet fully understood. This article collects and discusses the mechanisms of PM2.5-induced brain injury and self-repair after injury, which may provide new ideas for the prevention and treatment of cerebrovascular and cerebral neurological diseases.